On the Quantification of Mixing in Microfluidics. (October 2014) - Hashmi, Ali; Xu, Jie
Methods for quantifying mixing in microfluidics have varied largely in the past, and various indices have been employed to represent the extent of mixing. Mixing between two or more colored liquids is usually quantified using simple mathematical functions operated over a sequence of images. The function, usually termed mixing indices, involves a measure of standard deviation. Here, we first review some mixing indices and then experimentally verify the index most representative of a mixing event. It is observed that the relative mixing index is not affected by the lighting conditions, unlike other known mixing indices. Based on this finding, the use of a relative mixing index is advocated for further use in the lab-on-a-chip community for quantifying mixing events.